Pathogenesis of cerebral malaria—inflammation and cytoadherence - Storm, Janet; Craig, Alister G. (Frontiers in Cellular and Infection Microbiology, 2014)
Despite decades of research on cerebral malaria (CM) there is still a paucity of knowledge about what actual causes CM and why certain people develop it. Although sequestration of P. falciparum infected red blood cells has been linked to pathology, it is still not clear if this is directly or solely responsible for this clinical syndrome. Recent data have suggested that a combination of parasite variant types, mainly defined by the variant surface antigen, P. falciparum erythrocyte membrane protein 1 (PfEMP1), its receptors, coagulation and host endothelial cell activation (or inflammation) are equally important. This makes CM a multi-factorial disease and a challenge to unravel its causes to decrease its detrimental impact.